High salt intake during puberty leads to cardiac remodelling and baroreflex impairment in lean and obese male Wistar rats. Issue 6 (28th March 2020) - Rosa, G. B.; Cavalet, L. C.; de Melo, A. B. S.; Junior, M. D. F.; Lopes, P. R.; Cardoso, R. A.; Ferreira, L. A.; Tomé, F. D.; Nagib, P. R. A.; Celes, M. R. N.; Pedrino, G. R.; Castro, C. H.; et al.
Abstract: Modern lifestyle increases the prevalence of obesity and its co-morbidities in the young population. High-salt (HS) diets are associated with hypertension and cardiac remodelling. The present study evaluated the potential effects of cardiometabolic programming induced by HS intake during puberty in lean and obese rats. Additionally, we investigated whether HS could exacerbate the impairment of cardiovascular parameters in adult life due to postnatal early overnutrition (PO). At postnatal day 3 (PN3), twenty-four litters of Wistar rats were divided into two groups: normal litter (NL, nine pups/dam) and small litter (SL, three pups/dam) throughout the lactation period; weaning was at PN21. At PN30, the pups were subdivided into two more groups: NL plus HS (NLHS) and SL plus HS (SLHS). HS intake was from PN30 until PN60. Cardiovascular parameters were evaluated at PN120. SL rats became overweight at adulthood due to persistent hyperphagia; however, HS exposure during puberty reduced the weight gain and food intake of NLHS and SLHS. Both HS and obesity raised the blood pressure, impaired baro- and chemoreflex sensitivity and induced cardiac remodelling but no worsening was observed in the association of these factors, except a little reduction in the angiotensin type-2 receptor in the hearts from SLHS animals. Our results suggest that the response of newborn offspring to PO and juveniles to a HS diet leads to significant changes in cardiovascular parameters in adult rats. This damage may be accompanied by impairment of both angiotensin signalling and antioxidant defence in the heart.